2006
DOI: 10.1074/jbc.m606089200
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M Inhibits Adipogenesis through the RAS/ERK and STAT5 Signaling Pathways

Abstract: Adipocytes are a major energy reservoir, storing excess energy as lipids and releasing it on demand. In addition, adipocytes constitute an endocrine system by secreting soluble mediators known as adipokines, which regulate not only peripheral tissues such as muscles and adipose tissues but also the central nervous system (1). Disorders in adipose tissues are a major cause of the development of the metabolic syndrome, a common basis of type 2 diabetes and atherosclerotic vascular diseases (2). It is therefore i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 37 publications
4
60
0
1
Order By: Relevance
“…This finding is consistent with several previous studies that showed inhibitory effects of ERK activation on adipogenic differentiation. For example, stimulation with oncostatin M inhibited C/EBP␤-induced adipogenic differentiation through ERK signaling pathway in 3T3-L1 cells and mouse embryonic fibroblasts (51). Furthermore, apelin suppresses adipogenic differentiation through an ERK-dependent pathway in preadipocytes and mature adipocytes (52).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with several previous studies that showed inhibitory effects of ERK activation on adipogenic differentiation. For example, stimulation with oncostatin M inhibited C/EBP␤-induced adipogenic differentiation through ERK signaling pathway in 3T3-L1 cells and mouse embryonic fibroblasts (51). Furthermore, apelin suppresses adipogenic differentiation through an ERK-dependent pathway in preadipocytes and mature adipocytes (52).…”
Section: Discussionmentioning
confidence: 99%
“…2). Adipocytes are more than inert energy depots, and adipose tissue is a biologically active organ that carries out important (Green et al 1985;Kawai et al 2007) Antiadipogenic in primary rat preadipocytes (Wabitsch et al 1996b) and in human adipocytes (Wabitsch et al 1996a) Insulin/IGF-1 Proadipogenic Proadipogenic in 3T3-L1 cells (Green et al 1985;Smith et al 1988 Inhibitory Antiadipogenic in 3T3-L1 (Kawashima et al 1991), human marrow (Keller et al 1993), and human preadipocyte cells (Meng et al 2001) LTF Controversial No effect on 3T3-L1 adipogenesis (Hogan et al 2005;White et al 2008) Proadipogenic in 3T3-L1 cells (Aubert et al 1998) Antiadipogenic in bone marrow stromal cells (Gimble et al 1994) NP Inhibitory Antiadipogenic in 3T3-L1 cells (White et al 2008) OSM Inhibitory Antiadipogenic in 3T3-L1 cells (Miyaoka et al 2006;White et al 2008), mouse embryonic fibroblasts (Miyaoka et al 2006), and human adipose-derived mesenchymal cells (Song et al 2007) physiological processes including energy homeostasis and whole-body insulin sensitivity. Attenuating adipose tissue expansion can result in pathologies including insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that adipocytes in vitro and adipose tissue in vivo are responsive to gp130 cytokines (Balhoff and Stephens 1998;Stephens et al 1998;Lagathu et al 2003;Rotter et al 2003;Zvonic et al 2003Zvonic et al , 2004Tenney et al 2005;White et al 2008) and exert differential effects on adipogenesis. To date, no gp130 cytokines have been shown to promote adipogenesis, but as shown in Table 1, several cytokines in this family have been shown to inhibit adipocyte development (Keller et al 1993;Meng et al 2001;Zvonic et al 2003Zvonic et al , 2004Sopasakis et al 2004;Hogan and Stephens 2005;Miyaoka et al 2006;Song et al 2007;White et al 2008).…”
Section: Glycoprotein 130 (Gp130) Cytokinesmentioning
confidence: 99%
“…The majority of studies support a role for OSM in promoting metabolic dysfunction. For example, it is well documented that OSM inhibits adipogenesis (23,24). In addition, OSM induces plasminogen activator inhibitor-1 (PAI-1) expression in murine adipocytes (22) and in human AT (25).…”
mentioning
confidence: 99%